Overview of strategies that contribute to the environmental sustainability of pond aquaculture: rearing systems, residue treatment, and environmental assessment tools - Henares, Matheus N.P. [UNESP]; Medeiros, Mateus V. [UNESP]; Camargo, Antonio F.M. [UNESP] (Wiley, 2019)
Aquaculture is responsible for almost 50% of the global production of aquatic organisms. However, the activity generates residues that cause environmental impacts. Several strategies can be adopted from the planning stage to the residue treatment to reduce these negative impacts. Alternative rearing systems, such as integrated multi-trophic aquaculture (IMTA), integrated aquaculture-agriculture systems, recirculation systems (RAS) and biofloc (BFT), can be implemented in place of the traditional monocultures. At the residue treatment stage, the solids particles can be removed by the settlement of suspended solids in tanks or mechanical filters. The reduction in dissolved nutrients is used in biological filters, constructed wetlands or the irrigation of agricultural crops. Finally, we describe the methodologies that are used to estimate the aquaculture environmental impacts. These methodologies allow the stages and processes that have a higher environmental impact in the production chain to be identified. Among them, we can highlight the life-cycle assessment (LCA), emergy analysis and ecological footprint. The strategies described in this study can contribute to increasing aquaculture sustainability; however, studies should be developed that focus on more than just productivity and profitability, as it is necessary to include social and environmental issues.
Keywords: analysis of sustainability; effluent treatment; environmental impacts; management practices